Increased tropical cyclone intensification time in the western North Pacific over the past 56 years - Liguang Wu; Jun Lu; Xiaofang Feng (Environmental Research Letters, 2023)
It has been projected that the influence of anthropogenic climate change on tropical cyclone (TC) intensity could be detected by the end of the century although significant increasing trends in TC intensity metrics have been found based on the currently available historic records. The human influences on TC intensity have been debated for about two decades because of a lack of quantitative assessment of the contributions of large-scale environmental factors and track shifting. As an extension of a previous study, we show that the observed rise in the percentage of intense TCs in the western North Pacific basin over the past 56 years resulted from the combined influence of the track shifting and temporary changes in environmental factors. The influence of environmental factors was primarily owing to the decrease of environmental vertical wind shear and the warming of sea surface temperature (SST). While a small part of the observed rise in the percentage of intense TCs resulted from SST warming, the track shifting increased the TC intensification time by 18.2% (11.3 h) over the past 56 years, accounting for more than one-third of the observed percentage increase in intense TCs. Since track shifting is also projected in the global warming experiments, this study suggests that anthropogenic climate change may intensify TCs by shifting TC prevailing tracks.